GEOLOGY: FROM AN EARTH TO A PLANETARY SCIENCE IN THE TWENTIETH CENTURY - Marvin U.B. (My University, 2002)
Since the opening of the Space Age, images from spacecraft have enabled us to map the surfaces of all the rocky planets and satellites in the Solar System, thus transforming them from astronomical to geological objects. This progression of geology from being a strictly Earth-centred science to one that is planetary-wide has provided us with a wealth of information on the evolutionary histories of other bodies and has supplied valuable new insights on the Earth itself. We have learned, for example, that the Earth-Moon system most likely formed as a result of a collision in space between the protoearth and a large impactor, and that the Moon subsequently accreted largely from debris of Earth's mantle. The airless, waterless Moon still preserves a record of the impact events that have scarred its surface from the time its crust first formed. The much larger, volcanic Earth underwent a similar bombardment but most of the evidence was lost during the earliest 550 million years or so that elapsed before its first surviving systems of crustal rocks formed. Therefore, we decipher Earth's earliest history by investigating the record on the Moon. Lunar samples collected by the Apollo astronauts of the USA and the robotic Luna missions of the former USSR linked the Earth and Moon by their oxygen isotopic compositions and enabled us to construct a timescale of lunar events keyed to dated samples. They also permitted us to identify certain meteorites as fragments of the lunar crust that were projected to the Earth by impacts on the Moon. Similarly, analyses of the Martian surface soils and atmosphere by the Viking and Pathfinder missions led to the identification of meteorite fragments ejected by hypervelocity impacts on Mars. Images of Mars displayed landforms wrought in the past by voluminous floodwaters, similar to those of the long-controversial Channeled Scablands of Washington State, USA. The record on Mars confirmed catastrophic flooding as a significant geomorphic process on at least one other planet. The first views of the Earth photographed by the crew of Apollo 8 gave us the concept of 'Spaceship Earth' and heightened international concern for protection of the global environment.